(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
This paper employs Arendt’s political phenomenology to grasp climate change. However, climate change emerges in the broader framework of the ecological crisis. Indeed, Arendt’s thought offers relevant tools for this study. The first paragraph describes Arendt’s three worldly activities (labor, work, action), along with their conditions (nature, world, politics), and their temporalities (circularity, linearity, processualism). The second paragraph shows how the Industrial Revolution merged these activities and temporalities, transforming work into an endless process and bringing the unpredictability and irreversibility of action into nature. The last chapter discusses the ethical and political paths with an eye to Arendt’s thought.